White Mold: A Global Threat to Crops and Key Strategies for Its Sustainable Management - Md. Motaher Hossain; Farjana Sultana; Md. Tanbir Rubayet; Sabia Khan; Mahabuba Mostafa; Nusrat Jahan Mishu; Md. Abdullah Al Sabbir; Nabela Akter; Ahmad Kabir; Mohammad Golam Mostofa (Microorganisms, 2024)
White mold, caused by the fungal pathogen Sclerotinia sclerotiorum (Lib.) de Bary, is a significant biotic stress impacting horticultural and field crops worldwide. This disease causes plants to wilt and ultimately die, resulting in considerable yield losses. This monocyclic disease progresses through a single infection cycle involving basal infections from myceliogenically germinated sclerotia or aerial infections initiated by ascospores from carpogenically germinated sclerotia. The pathogen has a homothallic mating system with a weak population structure. Relatively cool temperatures and extended wetness are typical conditions for spreading the disease. Each stage of infection triggers a cascade of molecular and physiological events that underpin defense responses against S. sclerotiorum. Molecular markers can help rapid diagnosis of this disease in plants. Effective management strategies encompass altering the crop microclimate, applying fungicides, reducing inoculum sources, and developing resistant plant varieties. Integrated approaches combining those strategies often yield the best results. This review discusses the latest insights into the biology, epidemiology, infection mechanisms, and early detection of white mold. This review also aims to provide comprehensive guidelines for sustainable management of this destructive disease while reducing the use of excessive pesticides in crop fields.